2009
DOI: 10.2147/ppa.s4633
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of premature discontinuation of treatment in multiple disease states

Abstract: Background:Premature discontinuation of treatment impacts outcomes of clinical practice. The traditional perception has been patient discontinuation is mainly driven by unwanted side effects. Systematic analysis of data from clinical trials across several disease states was performed to identify predictors of premature discontinuation during clinical interventions.Methods:A post hoc analysis was conducted on 22 randomized, double-blind, placebo-controlled clinical trials for treatment of fibromyalgia, diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
2
19
1
1
Order By: Relevance
“…Common reasons for discontinuation include lack (or loss) of efficacy, AEs, patient decision (often for personal reasons such as transportation, inconvenience or relocation), physician decision (for reasons other than lack of efficacy or AEs), sponsor decision (the sponsor may decide that a patient should be discontinued following consultation with the investigator) and loss to follow-up (the patient did not attend a scheduled visit and could not be contacted). 16 Certolizumab pegol (CZP) is a humanised, PEGylated, anti-TNFa monoclonal antibody with high affinity for TNF and is administered subcutaneously. CZP is Fc-free and therefore does not display Fc-mediated cellular cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Common reasons for discontinuation include lack (or loss) of efficacy, AEs, patient decision (often for personal reasons such as transportation, inconvenience or relocation), physician decision (for reasons other than lack of efficacy or AEs), sponsor decision (the sponsor may decide that a patient should be discontinued following consultation with the investigator) and loss to follow-up (the patient did not attend a scheduled visit and could not be contacted). 16 Certolizumab pegol (CZP) is a humanised, PEGylated, anti-TNFa monoclonal antibody with high affinity for TNF and is administered subcutaneously. CZP is Fc-free and therefore does not display Fc-mediated cellular cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Butow & Sharp 2 , although not specifically addressing NP adherence, make and excellent summary of behavioral, cognitive and affective factors present in the non-adherence process. Other three studies have described the relationship between decreased pharmacological therapy efficacy to control pain as a major factor for discontinuing the drug, without however investigating in more detail psychosocial factors determining non-adherence [16][17][18] . Other studies were also found stressing the importance of considering psychosocial factors when selecting treatments, without however describing such aspects 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Bu yan etkiler orta şiddette ve geçicidir. Klinik veri çalışmalarına göre ilacı bırakmanın en yaygın iki nedeni arasında %40 hastada görülen yan etkiler ve %23 hastada görülen etkisizlik yer alır 23,24 .…”
Section: Serotonin Noradrenalin Geri Alım Inhibitörleri (Duloksetin unclassified